The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/mrm.22037
|View full text |Cite
|
Sign up to set email alerts
|

In vivo differentiation of two vessel wall layers in lower extremity peripheral vein bypass grafts: Application of high‐resolution inner‐volume black blood 3D FSE

Abstract: Lower extremity peripheral vein bypass grafts (LE-PVBG) imaged with high-resolution black blood three-dimensional (3D) inner-volume (IV) fast spin echo (FSE) MRI at 1.5 Tesla possess a two-layer appearance in T1W images while only the inner layer appears visible in the corresponding T2W images. This study quantifies this difference in six patients imaged 6 months after implantation, and attributes the difference to the T 2 relaxation rates of vessel wall tissues measured ex vivo in two specimens with histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…Regarding T1- versus T2-weighted lumen area differences, the lumen is on average 0.4 ± 0.9 mm 2 (95%CI: 0–0.9 mm 2 ) larger on T1-weighted images. This was not statistically significant, apparently contradicting earlier work [37] that studied a smaller population imaged at only 6 months after implantation. The earlier study found a statistically significant difference of 0.8 ± 0.6 mm 2 (95% CI 0.7–0.9 mm 2 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding T1- versus T2-weighted lumen area differences, the lumen is on average 0.4 ± 0.9 mm 2 (95%CI: 0–0.9 mm 2 ) larger on T1-weighted images. This was not statistically significant, apparently contradicting earlier work [37] that studied a smaller population imaged at only 6 months after implantation. The earlier study found a statistically significant difference of 0.8 ± 0.6 mm 2 (95% CI 0.7–0.9 mm 2 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Seven (47%) patients had coronary artery disease, 8 (53%) had diabetes mellitus, and 13 (87%) had hypertension. Four of the 7 patients imaged 6 months after implantation have been previously reported [37]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4g; channel border marked with arrows). To better visualize the 3D structure of scaffolds and channels, adoption of magnetic resonance (MR) microscopy (Mitsouras et al, 2009), a type of magnetic resonance imaging (MRI), may provide a practical solution (imaging will take less than an hour) of the entire scaffold crosssection. Scanning electron microscopy (SEM) at low magnification may also be conducive to visualize the cross-section of the constructed channel structure.…”
Section: Measurement Of Gelatin Droplet Volume and Channel Widthmentioning
confidence: 99%
“…For suspected complications, specialized imaging such as diffusion-weighted sequences for allograft function 53 and high-resolution vessel wall sequences 54,55 for rejection can be performed. These can be complementary to 3D high-spatial-resolution MR angiography and time-resolved sequences for arterial and venous separation.…”
Section: Future Directionsmentioning
confidence: 99%